2020
DOI: 10.3389/fnhum.2020.00307
|View full text |Cite
|
Sign up to set email alerts
|

Walking Time Is Associated With Hippocampal Volume in Overweight and Obese Office Workers

Abstract: Objectives: To investigate the long-term effects on cognition and brain function after installing treadmill workstations in offices for 13 months. Methods: Eighty healthy overweight or obese office workers aged 40-67 years were individually randomized to an intervention group, receiving a treadmill workstation and encouraging emails, or to a control group, continuing to work as usual. Effects on cognitive function, hippocampal volume, prefrontal cortex (PFC) thickness, and circulating brain-derived neurotrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…In Phase 2, pre-speci ed longitudinal mediation analyses will be performed on the entire MRI and PET/CT sample between changes in VO 2 peak, neurodegenerative measures, e.g., cognitive function and hippocampal volume, and in ammation levels between baseline and 24 months. In these models, we will determine how in ammation mediates the effect of exercise training on neurodegenerative measures, including global cognition, hippocampal volume, and grey matter in the posterior, anterior, and midcingulate cingulate cortex, respectively, using a set of linear regression and maximum likelihood estimations (132). Additionally, we will also test whether the exercise training intensity (supramaximal HIT vs. MICT) has a different mediating effect.…”
Section: Statistical Methods -Outcomesmentioning
confidence: 99%
“…In Phase 2, pre-speci ed longitudinal mediation analyses will be performed on the entire MRI and PET/CT sample between changes in VO 2 peak, neurodegenerative measures, e.g., cognitive function and hippocampal volume, and in ammation levels between baseline and 24 months. In these models, we will determine how in ammation mediates the effect of exercise training on neurodegenerative measures, including global cognition, hippocampal volume, and grey matter in the posterior, anterior, and midcingulate cingulate cortex, respectively, using a set of linear regression and maximum likelihood estimations (132). Additionally, we will also test whether the exercise training intensity (supramaximal HIT vs. MICT) has a different mediating effect.…”
Section: Statistical Methods -Outcomesmentioning
confidence: 99%
“…This lack of knowledge hinders employers and occupational health promoters from providing evidence-based support for office workers. A recent study targeting overweight and obese office workers reported that installing treadmill workstations did not significantly affect cognitive functions, but increased walking time was associated with increased hippocampus volume at 13 months follow-up [ 13 ]. Increased hippocampus volume has previously been associated with improved cognitive function, accompanied by increased cardiorespiratory fitness in older adults [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Though physical inactivity and sedentary behaviors are identified as potential health risks, only a fraction of the global population meets the global recommendations for PA [ 3 ]. The potential reason could be the mixed evidence on the association between sedentary behavior and insufficient activity with chronic disease risk, especially psychological and brain health [ 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%